Educational group and quality of life of hypertensive and diabetic elderly (Research, Society and Development, 2020)
The study aimed to compare the quality of life of hypertensive and diabetic elderly registered in Hiperdia, in a school health center in a city in the interior of São Paulo, participating in educational groups. Quantitative, analytical and cross-sectional study conducted with 264 elderly. Quality of life was assessed with Whoqol-bref of the World Health Organization. The results showed that 85 elderly had a frequency of less than 50% in educational activities and 179, greater than or equal to 50%. There were no significant differences in the mean domain scores when compared to the frequency of the elderly in the educational groups. It was concluded that there was no difference in quality of life between the two groups of elderly. The educational group is an important strategy for the control of diabetes and hypertension and helps in the quality of life. However, it is necessary to readjust its structure, directing the planning and service to the target audience, strengthening the bond between team and user, improving adherence and continuity of actions.